Implementación de Un Sistema de Información para la mejora del proceso administrativo de la empresa up and down inversiones sac - trujillo - Reátegui Leau, José Mauricio (2017)
This thesis had as starting point the analysis of the management processes of the Company UP AND DOWN SAC INVESTMENTS which was detected by data of students, instructors and payment control, are handled manually, which is time consuming and not very accurate, on the other hand cannot keep track of the exact assists students as to be manual and time based on the secretary forgets to check which means one day without pay. Due to the above exposed, we determined that implementation of a system optimized web business management INVESTMENT AND DOWN UP SAC and thanks to which sub-eliminated manual processes such as data entry of students, instructors and payment control, and others were automated as precise control of the assistance of students. After a study and analyze different methodologies to determine the most suitable was the Rational Unified Process (RUP) and together with the Unified Modeling Language (UML) allowed a better understanding of reality and system development. Platform was used. NET programming language, being complemented with Microsoft SQL Server 2008 R2 Express as database manager. As a result of this work we have a friendly and efficient system whereby achievement decrease time attendance report generation, optimizing the process and proposing new reports that support the decision making of the management.